Journaliste dans la guerre civile algérienne : Une profession intellectuelle entre littérature et politique - Tristan Leperlier (L’Année du Maghreb)
This article analyzes the evolution of the social status of the Algerian journalist in the intellectual field of Algeria during the «black decade» of the 1990s, through the prism of the literary field. The statistical approach coupled with the analysis of individual trajectories shows that journalism is an intermediate intellectual profession in the process of decommissioning (especially in relation to primary and higher education). The liberalization of the press after October 1988, however, allowed the profession to gain a great prestige, and to compete with the figure of the writer, until then paragon of the engaged intellectual, on the political terrain.